2018
DOI: 10.1128/cmr.00029-17
|View full text |Cite
|
Sign up to set email alerts
|

Candida auris: a Review of the Literature

Abstract: The emerging pathogen has been associated with nosocomial outbreaks on five continents. Genetic analysis indicates the simultaneous emergence of separate clades of this organism in different geographical locations. Invasive infection and colonization have been detected predominantly in patients in high-dependency settings and have garnered attention due to variable antifungal resistance profiles and transmission within units instituting a range of infection prevention and control measures. Issues with the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
505
4
25

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 453 publications
(540 citation statements)
references
References 74 publications
(198 reference statements)
6
505
4
25
Order By: Relevance
“…It is also possible that some of the reported isolates of C. haemulonii are misidentified as C. auris . It has been suggested that chromogenic agar is a low-cost method to differentiate between C. auris and C. haemulonii isolates 5. Molecular techniques are recommended to identify C. auris to the species level.…”
Section: Identification and Susceptibilitymentioning
confidence: 99%
See 4 more Smart Citations
“…It is also possible that some of the reported isolates of C. haemulonii are misidentified as C. auris . It has been suggested that chromogenic agar is a low-cost method to differentiate between C. auris and C. haemulonii isolates 5. Molecular techniques are recommended to identify C. auris to the species level.…”
Section: Identification and Susceptibilitymentioning
confidence: 99%
“…Molecular techniques are recommended to identify C. auris to the species level. Matrix-assisted laser desorption ionisation–time of flight mass spectrometry is capable of providing an accurate identification to the species level once spectra for C. auris are present in its database 5. The development of C. auris- specific PCR assays allows for rapid identification and are of particular use during outbreak settings 5.…”
Section: Identification and Susceptibilitymentioning
confidence: 99%
See 3 more Smart Citations